POLLEN MORPHOLOGY AND FRUIT MICROMORPHOLOGY OF THE GENUS Scandix (Apiaceae) - Demirpolat, Azize; Dogan, Gulden; Bagci, Eyup (Parlar Scientific Publications (P S P), 2021)
In this study; morphological features of pollen and the fruit micromorphology of 6 Turkish taxa belonging to the genus Scandix L. (S. stellata, S. aucheri, S. iherica, S macrorhyncha, S. halansae, S. pecten-veneris) were compratively examined for the first time, using light and scanning electron microscopy. The pollen grains of Scandix species are isopolar, radially symmetrical. The basic shape of the pollen grains in all studied taxa is purolate, except S. iberica, Pollen shape of S. iberica is perpurolate. In studied species ornemantasyon of pollen is usually rugulat and rugulate perforate. The apertured type is tricolporate with costae grains were seen in all species. The amb is triangular. S. stellato has the smallest pollen while S. iberica has the largest pollen. The fruit surface is usually akuleate (pointed thorns), tuberculate or flat. All akuleate fruits also have tubercles. Fruit cuticle is thick in other species, while it is thin in S. mocrorhyncha and S. halansoe. The fruit beak border is evident. Fruit micromorphology and palinological investigation of the genus Scandix has not been studied before. This study is important in order to provide data for other taxonomic studies to be done on Scandix genus.
Keywords: Scandix; Apiaceae; Pollen; Fruit micromorphology